Distributed computer and communication networks : 19th International Conference, DCCN 2016, Moscow, Russia, November 21-25, 2016, Revised selected papers /: 19th International Conference, DCCN 2016, Moscow, Russia, November 21-25, 2016, Revised selected papers. (2016) - Unknown
No abstract available